2017
DOI: 10.1007/s11302-017-9573-4
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of P2X7R by RNA interference in the hippocampus can attenuate morphological and behavioral impact of pilocarpine-induced epilepsy

Abstract: Cell signaling mediated by P2X7 receptors (P2X7R) has been suggested to be involved in epileptogenesis, via modulation of intracellular calcium levels, excitotoxicity, activation of inflammatory cascades, and cell death, among other mechanisms. These processes have been described to be involved in pilocarpine-induced status epilepticus (SE) and contribute to hyperexcitability, resulting in spontaneous and recurrent seizures. Here, we aimed to investigate the role of P2X7R in epileptogenesis in vivo using RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 90 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…Interestingly, P2X7R antagonists reduce the number and duration of spontaneous seizures and gliosis, which effects are maintained beyond treatment cessation (Jimenez-Pacheco et al, 2013 , 2016 ). The association between P2X7R antagonism and seizure suppression was confirmed by other research groups (Mesuret et al, 2014 ; Amhaoul et al, 2016 ; Amorim et al, 2017 ). Considering that increased expression of the P2X7R has been associated with down-modulation of the non-coding microRNA, miR-22, at the post-transcriptional level in a mouse model of status epilepticus (Jimenez-Mateos et al, 2015 ; Engel et al, 2017 ), we now set to compare the expression of P2X7R and miR-22 in epileptic brains and sera, respectively, of MTLE-HS patients.…”
Section: Introductionsupporting
confidence: 71%
“…Interestingly, P2X7R antagonists reduce the number and duration of spontaneous seizures and gliosis, which effects are maintained beyond treatment cessation (Jimenez-Pacheco et al, 2013 , 2016 ). The association between P2X7R antagonism and seizure suppression was confirmed by other research groups (Mesuret et al, 2014 ; Amhaoul et al, 2016 ; Amorim et al, 2017 ). Considering that increased expression of the P2X7R has been associated with down-modulation of the non-coding microRNA, miR-22, at the post-transcriptional level in a mouse model of status epilepticus (Jimenez-Mateos et al, 2015 ; Engel et al, 2017 ), we now set to compare the expression of P2X7R and miR-22 in epileptic brains and sera, respectively, of MTLE-HS patients.…”
Section: Introductionsupporting
confidence: 71%
“…Recently, the decrease of GSH level has been shown to induce cognitive decline and neuronal death during aging and neurodegenerative diseases [53,54]. Interestingly, P2X7R is a therapeutic target in the treatment of epilepsy [12][13][14]55]. Indeed, benzoylbenzoyl-ATP (BzATP, an P2X7R agonist) increases GSH concentration in the cerebrum through penicillin-induced epileptiform activity, which is reversed by A-438079, a P2X7R antagonist [56].…”
Section: Discussionmentioning
confidence: 99%
“…Suggesting an effect on the process of epileptogenesis, two studies showed P2X7R antagonism to decrease the mean kindling score in the rat PTZ kindling model [127,134]. Similar results were found using the rat pilocarpine model, where silencing of the P2X7R via siRNA resulted in reduced mortality, increased time to first spontaneous seizure, and reduced the number of spontaneous seizures [135]. In contrast, no effects on seizurefrequency via P2X7R antagonism was observed by Hong et al using a rat model where epilepsy development was induced via lithium-pilocarpine [118].…”
Section: Targeting Of the P2x7r And Seizure Controlmentioning
confidence: 56%